Modulating brain integrative actions as a new perspective on pharmacological approaches to neuropsychiatric diseases - Marcoli, Manuela; Agnati, Luigi F.; Franco, Rafael; Cortelli, Pietro; Anderlini, Deanna; Guidolin, Diego; Cervetto, Chiara; Maura, Guido (Frontiers in Endocrinology, 2023)
A critical aspect of drug development in the therapy of neuropsychiatric diseases is the “Target Problem”, that is, the selection of a proper target after not simply the etiopathological classification but rather the detection of the supposed structural and/or functional alterations in the brain networks. There are novel ways of approaching the development of drugs capable of overcoming or at least reducing the deficits without triggering deleterious side effects. For this purpose, a model of brain network organization is needed, and the main aspects of its integrative actions must also be established. Thus, to this aim we here propose an updated model of the brain as a hyper-network in which i) the penta-partite synapses are suggested as key nodes of the brain hyper-network and ii) interacting cell surface receptors appear as both decoders of signals arriving to the network and targets of CNS diseases. The integrative actions of the brain networks follow the “Russian Doll organization” including the micro (i.e., synaptic) and nano (i.e., molecular) levels. In this scenario, integrative actions result primarily from protein-protein interactions. Importantly, the macromolecular complexes arising from these interactions often have novel structural binding sites of allosteric nature. Taking G protein-coupled receptors (GPCRs) as potential targets, GPCRs heteromers offer a way to increase the selectivity of pharmacological treatments if proper allosteric drugs are designed. This assumption is founded on the possible selectivity of allosteric interventions on G protein-coupled receptors especially when organized as “Receptor Mosaics” at penta-partite synapse level